Cultura in vitro de micrósporos de trigo: efeito do pré-tratamento de espigas e do genótipo doador de ovários - Coelho, Mônica Bossardi (2017)
Wheat is one of the main food sources of the world´s population and represents the most widely grown cereal grain, occupying 17% of the total cultivated land around the globe. In Brazil, wheat production is not sufficient to supply the annual domestic consumption, leading the list of imports of the Brazilian trade balance. In order to change this scenario, genetic breeding programs have sought to produce new cultivars with better traits regarding superior yield and quality. This process, usually long, can be shortened through the production of double-haploid plants, considerably reducing the time to the development of new cultivars. Isolated microspore culture stands out as a promising biotechnological tool that could be efficiently applied to plant breeding programs. However, due to its high genotypic dependence, its application is hampered to be used in a large scale and routine practices. To overcome this limitation, the objective of this work was to improve the protocol of wheat isolated microspore cultur e, modifying plants exogenous factors that interfere in the response of the method, such as pre-treatments and ovary donor genotypes. The embryogenic response of three cultivars was evaluated: BRS 194, Embrapa 27 and Fielder, respectively known for producing: a) a large number of albino plants, b) negative control (highly recalcitrant) and c) positive control (highly responsive) to microspore culture. The spikes were submitted to different pre-treatments for induction of androgenesis, as cold (4 °C) used as the standard one. Ovary donor genotypes were also tested. The results showed a strong interaction between pre-treatments, genotypes and ovaries, with different responses for each treatment combination. The highest induction of androgenic response was obtained when Fielder was used as ovary donor, regardless of the pre -treatment applied to the spikes or the genotype. However, the status and physiology of donor plants greatly influenced the androgenic response, negatively affecting all three genotypes, including Fielder, the responsive control.